Analysis of the Internalisation of Tarekat Syadziliyah Values on Santri Pesantren Syaichona Moh. Cholil Bangkalan - Mardiyah, Mardiyah; Qusairi, Qusairi (EDUCATIO : Journal of Education, 2023)
The purpose of this study is to analyse the moral preservation efforts of Pondok Pesantren Syaichona Moh. Cholil Bangkalan in educating students through the teachings of Tarekat Syadziliyah. Pondok Pesantren Syaichona Moh. Cholil Bangkalan has a uniqueness in its method; namely, all students who are still teenagers actively follow the amaliyah of Tarekat Syadziliyah. The research method used is a qualitative approach with the type of case study, which describes how the internalisation of Tarekat Syadziliyah values affects the moral formation of santri. Research data were obtained through interviews, observations, and collection of documentation data related to the research subject. Data validity test was conducted using the triangulation technique. The results of this study explain two main aspects—first, the morals of students developed at the Syaichona Moh. Cholil Bangkalan Islamic Boarding School include morals towards God, the Prophet Muhammad, personal morals, morals in the family, and state morals. Second, the internalisation of Tarekat Syadziliyah values in shaping the morals of santri is carried out through faith, amaliyah, scientific, moral, and social education. Through this approach, Syaichona Moh. Cholil Bangkalan Islamic Boarding School has succeeded in forming good santri morals and contributing to the formation of their character as individuals with noble morals.